PEMBERDAYAAN IBU RUMAH TANGGA SEBAGAI UPAYA MENGEMBANGKAN KEMANDIRIAN DAN BUDAYA KREATIF PENDIDIKAN ANAK USIA DINI ALMUKMIN DI KELURAHAN WAY KANDIS BANDAR LAMPUNG - Heny Herawati; Rasty Yulia (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
Early childhood is a sensitive period for a child inside develop various abilities. There are sensitive timesmaturation of psychic functions that are ready to respond to that stimulation provided by the environment. This is the time to lay the foundations first in developing physical abilities, cognitive, self-concept, discipline, independence, arts, morals and religious as well as social and emotional values. Social development that begins at birth will grow rapidly during early childhood. Children at this age learn how socializing, including learning how to understand other people's point of view other. At this time mental activity originates from social contact and relationships with others. The social contact what children do at this age encourages the development of social competence in child. This includes developing independence. Many social factors can be an obstacle to development social competence in children, social factors such as life inadequate family, parents or neighbors involved in the behavior crime, as well as violence and the ineffectiveness of the atmosphere and relationships in the school environment. As is known, currently many parents are working outside the home so they have to leave the care of the child to someone else. Interaction intense interaction between the caregiver and the child will affect the child's development the. There are still many parents who do not think what to give on their child's caregiver or what kind of parenting provision for the child they can still develop optimally with the help of caregivers or the household assistant. Basically, many teachers or parents complain about the development of independence and responsibility for the level of creativity of their children.